Eridu. A Preliminary Communication on the First Season’s Excavations. January-March 1947 - al Asil, Naji
Foreword (Naji al Asil) — 1. Introduction (Seton Lloyd) — 2. History of Eridu (Fuad Safar) — 3. The Excavations: Temples VI and VII; Temples I-V; Building in Square 5/4; The Eridu Lion (Fuad Safar).